Phenotypic characteristics of B cells in Behçet's disease: increased activity in B cell subsets - (:unkn) unknown (My University, 1999)
OBJECTIVE: Increased numbers of spontaneous Ig secreting B cells and elevated immunoglobulin levels have been described in Behçet's disease (BD), in addition to changes in numbers and activities of T cells, natural killer cells, and monocyte-macrophages. We investigated other characteristics of B cells in BD. METHODS: B lymphocyte subsets (CD19+CD5+, CD19+CD13+, CD19+CD28+, CD19+CD33+, CD19+CD80+, CD5+CD19+CD45RA+, CD5+CD19+CD45RO+) were phenotypically evaluated in 50 patients with BD, 80 healthy subjects, and 20 other patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and sepsis. RESULTS: Although the B cell number (CD19+) was normal, CD13 and CD33 positive B cells were more numerous in BD and sepsis compared to healthy controls and patients with RA and SLE. The percentage of CD45RO positive B cells was higher in both BD and sepsis, while the percentage of CD80 positive B cells was high only in BD. There was no increase in the CD5+CD19+ B cell subset, previously shown to be increased in several autoimmune diseases. Naive (CD45RA) and memory (CD45RO) status of CD5+CD19+ and CD5-CD19+ B cells showed that CD45RA expression was higher in CD5+CD19+ B cells, whereas expression of both CD45RA and CD45RO was higher in the CD5-CD19+ B cell group compared with healthy controls. CONCLUSION: Although the total B cell number was normal, increased levels of activated and memory B cell subsets suggest a modified B cell function in BD, which may be related to a weak stimulus by an unknown external antigen.
Keywords: Adult; Female; Humans; Middle Aged; Behcet Syndrome; Aged; Male; Flow Cytometry; Sepsis; Arthritis, Rheumatoid; Immunophenotyping; Lupus Erythematosus, Systemic; Lymphocyte Count; Antigens, CD; B-Lymphocyte Subsets